ASSESSING KNOWLEDGE OF HAND HYGIENE AMONG CBME AND NON-CBME MEDICAL UNDERGRADUATES: A QUESTIONNAIRE-BASED SURVEY - Balaraman, Ramani; Manavalan, Jayavarthinni; Banaji, Nandita (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to evaluate the knowledge of hand hygiene among CBME and non-CBME medical undergraduates. Methods: A descriptive cross-sectional questionnaire-based study was carried out among 390 medical undergraduate students of CBME (1st, 2nd, and 3rd year) and non-CBME batches (4th year and interns). The data collection tool containing 25 close-ended questions from WHO’s “Hand Hygiene Knowledge Questionnaire for Health-Care Workers” was circulated to the participants as Google forms. Each correct response was given a score of “1” and each wrong response was given a score of “0”. Based on the total score obtained, the knowledge level of hand hygiene of each participant was categorized into good, moderate, or poor. Data were analyzed using OpenEpi software. Results: A total of 390 medical students including interns participated in this study, of which 222 (57%) were from the CBME batch and 168 (43%) were from the non-CBME batch. Of the 25 questions, >75% of the participants responded correctly to 13 questions. Statistical significance (p<0.05) was observed with 5 questions in which the non-CBME students had better knowledge than CBME students. However, most of the participants (n=288) had a moderate level (73.85%) of knowledge of hand hygiene. Conclusion: The knowledge gap about hand hygiene could lead to avoidance of regular usage of hand rub and poor compliance with it. Hence, it is important to address it during training sessions to ensure better hand hygiene practices.